Piezoelectric-Based Vibration Control From Macro to Micro/Nano Scale Systems - Jalili, Nader; SpringerLink (Online service) (Boston, MA : Springer US : Imprint: Springer, 2010)
Piezoelectric-Based Vibration Control: From Macro to Micro/Nano Scale Systems covers a comprehensive understanding and physical principles in piezoelectric materials and structures used in a variety of vibration-control systems. With its self-contained and single-source style, this book provides a widespread spectrum of discussions ranging from fundamental concepts of mechanical vibration analysis and control to piezoelectric actuators and sensors. Starting from an elementary level in mechanical vibrations, this book Offers the reader a detailed discussion of vibration of continuous systems as a single-source book, Provides actual actuator and sensor configurations, along with illustrative hands-on problems and examples that can be applied by the reader, and Covers advanced topics in piezoelectric-based micro/nano actuators and sensors with applications ranging from precision mechatronics to molecular recognition and functional nanostructures. Piezoelectric-Based Vibration Control: From Macro to Micro/Nano Scale Systems, with its easy-to-follow format, is a must-read for all engineers working in the areas of vibration control and piezoelectric systems, undergraduate students interested in fundamental of vibrations and control, up to graduate students and researchers working on advanced piezoelectric-based vibration-control systems.
and Overview of Mechanical Vibrations -- An Introduction to Vibrations of Lumped-Parameters Systems -- A Brief Introduction to Variational Mechanics -- A Unified Approach to Vibrations of Distributed-Parameters Systems -- Piezoelectric-Based Vibration-Control Systems -- An Overview of Active Materials Utilized in Smart Structures -- Physical Principles and Constitutive Models of Piezoelectric Materials -- Hysteretic Characteristics of Piezoelectric Materials -- Piezoelectric-Based Systems Modeling -- Vibration Control Using Piezoelectric Actuators and Sensors -- Piezoelectric-Based Micro/Nano Sensors and Actuators -- Piezoelectric-Based Micro- and Nano-Positioning Systems -- Piezoelectric-Based Nanomechanical Cantilever Sensors -- Nanomaterial-Based Piezoelectric Actuators and Sensors.
Keywords: Engineering; Vibration; Mechanical engineering; Electronics; Nanotechnology; Engineering; Control, Robotics, Mechatronics; Vibration, Dynamical Systems, Control; Nanotechnology; Mechanical Engineering; Electronics and Microelectronics, Instrumentation